Glicerol como substrato para a produção de biossurfactante por Pseudomonas aeruginosa UCP0992. - Silva, Selma Neide Rodrigues Lopes (2010)
Surfactants are amphipathic agents with application in different industries, such as the petroleum, food and pharmaceutical. Many kinds of chemical surfactants are being used nowadays, although the development of alternative products, with biodegradable nature and lower toxicity, as the so called biosurfactants, metabolites from microorganisms, is a sound strategy for the development of compounds with ecological acceptability and for the knowledge of specific properties and application of these compounds. Different biosurfactants have been produced, but few are being commercialised due the high production costs regarded the utilisation of substrates and purification techniques. Thus, the purpose of this work is to combine the glycerol generated from biodiesel at low cost with the ability of the bacterium Pseudomonas aeruginosa UCP0992 to produce a biosurfactant with ability to remove a hydrophobic pollutant from the petroleum industry. First, the influence of glycerol concentration (2-7%), of type (NaNO3, NH4NO3, urea, (NH4)2SO4, peptone, yeast extract and corn steep liquor), and concentration (0,05-0,6%) of the nitrogen source and of the cultivation conditions (temperature – 28 and 37ºC, aeration – 60, 80 and 90% and agitation – 150 and 200 rpm) was studied for biosurfactant production by Pseudomonas aeruginosa UCP0992. The kinetic of growth and production of the biosurfactant has been described for the medium supplemented with 3% glycerol and 0.6% NaNO3, at 28 ºC during 120 hours under 200 rpm. A parallel relation between biomass, consume of glycerol, biosurfactant production, surface tension reduction and hexadecane emulsification showed a growth-associated production. The isolated biosurfactant corresponded to a yield of 8.0 g/L after 96 hours with a biomass of 4.0 g/L. The medium surface tension was reduced from 56 mN/m for 27,4 mN/ and the hexadecane emulsification remained unchanged after 72 hours, with values around 75%. The biosurfactant showed a CMC of 700 mg/L an interfacial tension against hexadecane of 2 mN/m, thermal (4-120ºC) and pH (4-12) stability regarding the surface tension reduction and the emulsification capacity of vegetable oils and diesel, and tolerance under salt concentrations (2-10%). Little changes in the surface tension and in the emulsification activity were observed when the cell-free broth containing the biosurfactant was submitted under 90°C during two hours. The biosurfactant has been characterized as a group of rhamnolipids with anionic nature. The crude biosurfactant did not show toxicity against the micro crustacean Artemia salina and the cabbage (Brassica oleracea) in the conditions tested, while the isolated biosurfactant showed toxicity against the micro crustacean depending on the concentration used. The potential application of the biosurfactant in petroleum and diesel recovery from sand was demonstrated by the percentiles of oils removal (85%). The promising results obtained in this work are noteworthy for possible biosurfactant production from glycerol.